HUBUNGAN TINGKAT PENGETAHUAN TENTANG GIZI DENGAN KEJADIAN KEKURANGAN ENERGI KRONIK PADA REMAJA - Tatirah Tatirah; Ziyadatul Chusna Almabruroh Yuni Alfi; Resya Tri Utami (Lembaga Penelitian & Pengabdian Masyarakat Sekolah Tinggi Ilmu KesehatanBrebes, 2023)
Background: Adolescents who have malnutrition status or often called malnutrition, if it has been too long then there will be Chronic Energy Deficiency (CED). Chronic Energy Deficiency (CED) is a condition in which a person suffers from a lack of nutritional intake, energy and protein that lasts a long time or chronic. The purpose of this study was to determine the relationship between the level of knowledge of adolescent girls about nutrition with the incidence of Chronic Energy Deficiency (CED) in adolescence. Method: This type of research uses analytical research methods with a Cross Sectional approach. Bivariate analysis is used to determine the relationship to the object of study using the chi square test. This research was conducted at the Al-Falah Shofwaniyah Islamic Boarding School in Jatirokeh using primary data with questionnaire sheets as research data. The subjects of the study were adolescent girls with a sample of 37 respondents using a total sampling system. Results: The results of the study found that adolescent girls had good nutritional knowledge with the incidence of CEDs obtained by 20 people with a level of knowledge of good nutrition in adolescents not CEDs as many as 2 people, while adolescent girls had sufficient knowledge with the incidence of CEDs as many as 2 people with a sufficient level of nutritional knowledge in adolescents not CEDs as many as 13 people. The results of statistical tests using chi square analysis obtained a value of p > 0.979. Conclusion: the results of the study stated that there was no relationship between nutritional knowledge and Chronic Energy Deficiency (CED).